Technique for Orthodontic Clinical Photographs Using a Smartphone - Al Imran Shahrul; Nabilla Shukor; Noraina Hafizan Norman (International Journal of Dentistry)
Smartphone cameras have advanced at a rapid rate. With this advancement, it is possible to take high quality orthodontic clinical photographs using a smartphone. The aim of this article is to describe the technique to take orthodontic clinical photographs using a smartphone.